2012
DOI: 10.1016/j.nuclphysa.2012.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Local violation effects and thermalization in QCD: Views from quantum field theory and holography

Abstract: We argue that the local violation of P and CP invariance in heavy ion collisions and the universal thermal aspects observed in high energy collisions are in fact two sides of the same coin, and both are related to quantum anomalies of QCD. We argue that the low energy relations representing the quantum anomalies of QCD are saturated by coherent low dimensional vacuum configurations as observed in Monte Carlo lattice studies. The thermal spectrum and approximate universality of the temperature with no dependenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 144 publications
(409 reference statements)
2
34
0
Order By: Relevance
“…The first issue we address is the question about the favoured angle, ϕ, between the two boundaries, (30) and (31). In order to find the angle we chose (arbitrarily) N = 7 and varied the angle in the range [−π, π] − 8π/7, and look at the action S 1 as a function of ϕ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first issue we address is the question about the favoured angle, ϕ, between the two boundaries, (30) and (31). In order to find the angle we chose (arbitrarily) N = 7 and varied the angle in the range [−π, π] − 8π/7, and look at the action S 1 as a function of ϕ.…”
Section: Resultsmentioning
confidence: 99%
“…This identification would justify the effective Lagrangian approach advocated in [28,30] wherein θ( x, t) ind is treated as slow background field with correlation length much larger than any conventional QCD fluctuations, L Λ −1 QCD . It is important to emphasize that the P and CP symmetries are good symmetries of the fundamental QCD.…”
Section: Resultsmentioning
confidence: 99%
“…[32] for the details. In particular, the local violation of the CP invariance observed at RHIC (Relativistic Heavy Ion Collider) [33] and LHC (Large Hadron Collider) [34] have been interpreted in [32,35,36] as an outcome of a charge separation mechanism in the presence of the induced θ ∼ 1 resulting from a collision. The difference is of course that CP odd term with θ ∼ 1 discussed in cosmology describes a theory on the horizon scale, while θ ∼ 1 in heavy ion collisions is correlated on a size of the colliding nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…To be more specific, it was suggested a while ago [64][65][66][67][68] that the so-called induced theta vacua jθ ind i can be created in heavy ion collisions. This direction of studies became a very active area of research after an appropriate observational signature had been suggested [69] and theoretical computations of the effect had been put on a solid theoretical ground [70]; see also related papers [71][72][73] with specific applications to heavy ion collisions, and also review paper [74] which covers some recent theoretical development. The experimental studies at the relativistic heavy ion collider (RHIC), Brookhaven [75], and, more recently, at the LHC [76] apparently support the basic picture advocated in [69][70][71][72][73][74].…”
Section: Generalization To Four-dimensional Qcdmentioning
confidence: 99%
“…The basic idea advocated in [69][70][71][72][73][74] can be explained as follows in a few lines. Let us assume that an effective θðx; tÞ ind ≠ 0 is induced as a result of some nonequlibrium dynamics, as suggested in Refs.…”
Section: Generalization To Four-dimensional Qcdmentioning
confidence: 99%